Character & leadership a sacred trust - Barry, Thomas J. (Universiti Utara Malaysia Press, 2002)
This book is a unique approach to your own personal definition of character and leadership. It takes you on a journey into new areas of how character and leadership come together in your own life. This book may change your perceptions and it will create awareness, acceptance and action at some level.